2022
DOI: 10.3390/plants11121614
|View full text |Cite
|
Sign up to set email alerts
|

Callus-Mediated High-Frequency Plant Regeneration, Phytochemical Profiling, Antioxidant Activity and Genetic Stability in Ruta chalepensis L.

Abstract: Efficient methods for callus induction and the high-frequency plant regeneration of Ruta chalepensis L. were established, and the phytochemical potential and antioxidant activity of a donor plant, ex-vitro-established micropropagated plants, and callus were also studied. Yellowish-green callus was induced with a frequency of 97.8% from internode shoot segments of the donor plant growing in soil in the botanical garden cultured on Murashige and Skoog (MS) medium containing 10 μM 2,4-D (2,4-dichlorophenoxyacetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 85 publications
0
5
0
1
Order By: Relevance
“…In this regard, Rai and his research team [ 30 ] showed that using BA in a concentration of 1 mg/L achieved a high number of buds of P. guajava while increasing the concentration to 2 mg/L induced a sharp decrease in bud formation. Other research groups [ 31 , 32 ] have reported the same observation they found that high concentrations of cytokinin have deleterious effects on the multiplication of shoots in Aspilia africana and Ruta chalepensis , respectively. BA as an adenine cytokinin promotes cell division in plant tissues; hence increasing its level will increase the number of cells, subsequently with cell contents, and the percentage of absorbed water in the cell tissues.…”
Section: Resultsmentioning
confidence: 60%
“…In this regard, Rai and his research team [ 30 ] showed that using BA in a concentration of 1 mg/L achieved a high number of buds of P. guajava while increasing the concentration to 2 mg/L induced a sharp decrease in bud formation. Other research groups [ 31 , 32 ] have reported the same observation they found that high concentrations of cytokinin have deleterious effects on the multiplication of shoots in Aspilia africana and Ruta chalepensis , respectively. BA as an adenine cytokinin promotes cell division in plant tissues; hence increasing its level will increase the number of cells, subsequently with cell contents, and the percentage of absorbed water in the cell tissues.…”
Section: Resultsmentioning
confidence: 60%
“…Although plant genetic stability was put under validation in cases where undifferentiated explants like cell suspension or callus were used as plant material due to some tissue culture protocols and in vitro preservation (Tahtamouni et al, 2017;Qahtan et al, 2022), our results revealed that genetic makeup was unaltered in callus and cell suspension cultures (Fig. 3 and 4).…”
Section: Effect Of In Vitro Propagation On Genetic Stability Of S Nig...mentioning
confidence: 70%
“…The comparative metabolite profiling of in vivo and in vitro grown root tissues displayed variation in several detected phytocompounds level. The increased production of phytocompounds in the in vitro derived root (compared to intact in vivo plant tissues) may be attributed to various factors such as media composition, hormonal concentration, genotype, photoperiod, temperature, etc., [13,38] and thus, could be a more potent and reliable source of phytocompounds for pharmacological uses. Previously, Vijayalakshmi and Shourie [39] reported the presence of variety of phytochemicals in leaf, stem, and leaf derived callus in G. glabra.…”
Section: Discussionmentioning
confidence: 99%